The Impact of Video Modeling on Improving Social Skills in Children with Autism - Alzyoudi, Mohammed; Sartawi, AbedAlziz; Almuhiri, Osha (Journal of the American Academy of Special Education Professionals, 2014)
Children with autism often show a lack of the interactive social skills that would allow them to engage with others successfully. They therefore frequently need training to aid them in successful social interaction. Video modeling is a widely used instructional technique that has been applied to teach children with developmental disabilities such as autism. Previous research involving children with autism has shown that video modeling can be effective in teaching a variety of skills. The aim of this study is to evaluate the impact of video modeling on social skills development in children with autism. A small sample of five boys with autism was chosen to participate in this study. The boys ranged in age between five and seven years. Each child was asked to watch a video tape which presented two individuals interacting in a role play setting. One person portrays a therapist giving cues, whilst the second portrays a child acting appropriately and demonstrating correct social behaviors. The boys were then asked to complete a social task and their performance was compared against baseline assessment measures. The results of this study indicate this method is an effective method for instruction. Results are discussed and implications for further research and practice are provided.